NK Cells in a Tug-of-War With Cancer: The Roles of Transcription Factors and Cytoskeleton - Lee, E Hui Clarissa; Wong, Darren Chen Pei; Ding, Jeak Ling (Frontiers in Immunology, 2021)
Natural killer (NK) cells are innate immune cells which play a key role in shaping the immune response against cancer. Initially hailed for their potential to recognise and eliminate tumour cells, their application has been greatly hindered by the immunosuppressive tumour microenvironment (TME) which suppresses NK functions (e.g., cytotoxicity). This dysfunctional state that is accompanied by phenotypic changes such as upregulation of inhibitory receptors and downregulation of activating receptors, forms the basis of what many researchers have referred to as ‘exhausted’ NK cells. However, there is no consensus on whether these phenotypes are sufficient to define an exhausted state of the NK cell. While recent advances in checkpoint inhibition appear to show promise in early-stage pre-clinical studies, much remains to be fully explored and understood in the context of the TME. The TME is where the NK cells are subjected to interaction with various cell types and soluble factors, which could exert an inhibitory effect on NK cytotoxicity. In this review, we provide an overview of the general markers of NK cell exhaustion viz, the surface activating and inhibitory receptors. We also highlight the potential role of T-box transcription factors in characterising such a dysfunctional state, and discuss the often-overlooked mechanism of cell cytoskeletal dynamics in regulating NK cell function. These aspects may further contribute to NK exhaustion or NK revival in cancer, and may open new avenues to explore cancer treatment strategies. (233 words)